The " complex" in the humanities. a proposal for the update from the participatory seminars - Espinosa Brilla, Dina (2013)
It is important to point out the way in which the 'General Studies' School, particularly with the introduction of  'Participative Seminars' since 1974, has incorporated a methodological option in accordance with the cognitive models suggested by the University of Costa Rica' statutory mandate.  Also, the “Humanities for the XXI century” are revised according to international standards of college education quality. Such pathways convey to the strenghtening of methodological strategies based on the complexity paradigm.